Sistem Rekomendasi Pemilihan Siswa Berprestasi MenggunakanMetode Simple Additive Weighting( Studi Kasus : SMK Widya Karya Purwokerto ) - Linda Apriyanti; Siti Yuliyanti; Yoga Helfiyan (Jurnal Teknologi Informasi dan Komunikasi, 2021)
Selection of outstanding students is very necessary in a school, because schools need to know which students are superior in the school. Problems arise when these developments are not accompanied by a system that supports the selection of high achieving students who are right and according to the criteria. The purpose of writing this thesis is to build a system that can assist teachers in determining student achievement according to the criteria. In this system, the Simple Additive Weighting method is used as a basis for normalizing the inputted weights and is used to determine thestudent's highest score alternative as a system recommendation. The process of determining the decision support system is carried out using the existing value in the report card The results of the decisions obtained from this system indicate that this method is more effective in determining the correct achievement students and according to the criteria for academic scores, activeness scores, attendance values and personality values as a comparison in determining the final result.